Multi Helix Collaboration Model as A Policy Instrument of Tourism Village Policy in Pujon Kidul Tourism Village - Fitriana, Annisa Nur; Wijaya, Andy Fefta; Wanto, Alfi Haris; Anantanatorn, Anurat (Journal of Local Government Issues, 2025)
The Multi-Helix Innovation Model offers a comprehensive framework for addressing complex issues through the collaboration of various stakeholders, including government, private sector, academia, and civil society.  This study explores the application of the Multi-Helix Innovation Model as a policy instrument in the development and governance of Pujon Kidul Tourism Village, Indonesia. It examines how stakeholder collaboration shapes tourism policies, improves resource management, and fosters economic growth, facilitating sustainable development, innovation, and community participation. Using a descriptive qualitative method, the research identifies gaps in the implementation of collaborative governance, particularly in the underutilization of media and other stakeholders. By integrating Grindle's policy implementation theory and the Collaborative Governance Plus Multi-Helix framework, this study fills a research gap and provides a comprehensive approach to rural tourism development. The study concludes that the Multi-Helix Innovation Model offers a promising framework for enhancing tourism competitiveness while preserving local culture and environment, guiding future policy for sustainable rural development.